Patient with recurrence dermatofibrosarcoma protuberans: A case report - Amjadzadeh, Mohammadreza (Clin Case Rep, 2020)
We present a typical case of dermatofibrosarcoma protuberans(DFSP) with a complaint of a painful and various recurrence, make a review of the most important aspects. This is a rare tumor and we call special attention to the fact that its recurrence is extremely frequent, so there is absolute need to observe these patients periodically after surgery.